Scaling up local development initiatives: Brazil's food acquisition programme - Ryan Nehring; Ben McKay (International Policy Centre for Inclusive Growth (IPC-IG), 2013)
[Introduction ...] The paper begins in Section 2 by providing an overview of the design, operations and trajectories of the PAA. We explore the actors involved in the design and the different implementation modalities (i.e. purchase from individual farmers and associations and organisation of purchase by the national supply company, local municipalities and states). The actual steps that need to be followed in the procurement process are also outlined with a view to highlighting some of the key issues that will have a bearing on scaling up the programme in terms of the scale of its scope and reach to some of the more vulnerable family farmers. Section 3 outlines the objectives of this study which are to (i) to provide first-hand documentation of the design and operations of the programme - which includes the observed physical actors - involved in design and implementation; and (ii) to identify the potential for scaling up the programme in country and the possibilities for South-South knowledge-building. Desk research is informed by field research in the states of Piauí and Ceará, both of which are in the north-eastern region of Brazil. This region has the highest incidence of extreme poverty in the country, a major share of which is located in rural areas. Consequently, the federal government sees the expansion of the PAA as a crucial instrument to achieve its goal of eliminating extreme poverty, especially in the north-eastern region. Piauí is one of the states that has most deployed the PAA-Estadual modality. Ceará was chosen to observe the PAA-Municipal modality which is not present in Piauí. Section 4 then looks at issues of recent policy developments and scaling up, particularly at the level of expanding coverage for the extreme poor. Expansion of the programme can be analysed in terms of different pathways (Linn/IFPRI, 2012). Geographical expansion or expanding coverage to a particular population under the programme could follow a `horizontal' duplication in new areas. The addition or modification of modalities could represent a `functional' expansion through new methods to increase participation. Institutional expansion across local, state or national levels indicates a `vertical' expansion. The paper argues that, due to the multi-stakeholder design of the programme, it is expanding through all three of the above pathways under the federal government's new strategy to eliminate extreme poverty. The paper also looks at the specific issues of how to reach hitherto unreached populations and how to cover current programme participants more effectively. The following sections go on to explore key issues and challenges with regard to scaling up such as organisational capacities of farmers, transportation, design of payment systems and financing. The approach taken by Brazil's PAA, including recent developments, is considered, and the issues that are likely to be of most interest from the point of view of South-South knowledge-sharing are highlighted.
Keywords: 330